Study of the criteria of psychometrics of psychodiagnostics methods and its content (MMIT Proceedings, 2025)
The article presents detailed thoughts on the psychometric criteria of psychodiagnostic methods, its essence, application in science, the fact that the measurement of phenomena in psychology is a process consisting of determining the degree to which an object or a set of objects possesses a certain property, and if the measurement relates to a characteristic or property inherent in a person, then it is natural that this property is inherent in him to varying degrees. In addition, it is stated that a measure is a method of placing the characteristics of a person or a group of people in a continuum (scale) in relation to one of its characteristics, the measure is mainly a quantitative process, consisting in assigning numerical values to events, objects, and the rules for assigning numerical values to events determine the usefulness of the measure.